Pengaruh Penggunaan Smartphone Terhadap Perubahan Perilaku Siswa (Studi Kasus Siswa Sekolah Menengah Atas Negeri 5 Palembang) - Muhammad Miftah Farid; Hafid Furqon (Universitas Islam Negeri Raden Fatah Palembang, 2018)
The era of Technology and Information which is now completely practical and fast certainly makes many people want to try to participate in it. Smartphones are smart phones that have evolved to this day become a tool that can be used by many people to not only communicate, but also to entertain themselves, to get information, learn to work and online selling. Smartphones are getting more and more years, so they are growing rapidly, especially to the millennial generation and the current generation Z is feared to be able to influence changes in their daily behavior. Smartphones that become daily needs for teenagers will certainly be viewed from various sides, whether a big positive and negative affect on the behavior that they apply every day. The number of smartphone users from existing data shows the amount of enthusiasm of teenagers to access the internet through smartphones. This research was made with the title